1997
DOI: 10.1002/(sici)1096-9861(19970623)383:1<1::aid-cne1>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and substrate properties of agrin, a heparan sulfate proteoglycan of developing axonal pathways

Abstract: The distribution and substrate properties of agrin, an extracellular matrix heparan sulfate proteoglycan (HSPG), was investigated in the developing chick nervous system by immunocytochemistry, Western blotting, and in neurite outgrowth assays. By comparing the distribution of agrin with that of laminin-1, merosin (laminin-2), neurofilament, and neural cell adhesion molecule (NCAM), it was found that throughout development, agrin is a constituent of all basal laminae. From embryonic day (E) 4 onwards, agrin is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 87 publications
4
42
0
Order By: Relevance
“…Agrin staining in the brain is most prominent in the blood vessels and in pial basement membranes (Barber and Lieth, 1997;Halfter et al, 1997). Moreover, neurons in the CNS have been shown to express mRNA encoding agrin isoforms that contain amino acid inserts at the B/z site (O'Connor et al, 1994;Stone and Nikolics, 1995).…”
Section: Agrin Localizes To Excitatory But Not Inhibitory Synapses Inmentioning
confidence: 83%
“…Agrin staining in the brain is most prominent in the blood vessels and in pial basement membranes (Barber and Lieth, 1997;Halfter et al, 1997). Moreover, neurons in the CNS have been shown to express mRNA encoding agrin isoforms that contain amino acid inserts at the B/z site (O'Connor et al, 1994;Stone and Nikolics, 1995).…”
Section: Agrin Localizes To Excitatory But Not Inhibitory Synapses Inmentioning
confidence: 83%
“…The 39.4D5 and H5 mAbs, which recognize antigens islet-1 and vimentin, respectively, were used to reveal retinal ganglion cells (Fischer et al, 2002) and M€ uller cells (Fischer et al, 2004), which were present in low numbers in some ILM/ MCEF sheets. Laminin and agrin, two components of the ILM, were recognized with 3H11 and 6D2 mAbs (Halfter et al, 1997), respectively. MCEF were labeled with JG22 mAb, which was raised against the b1 subunit of avian integrins (Hofer et al, 1990;Hynes, 2004); in the retina, this mAb specifically labels the surface of developing and mature M€ uller cells and is highly concentrated at their end-feet (Hering et al, 2000).…”
Section: Immunofluorescence Labeling Of Ilm/mcef Sheet Culturesmentioning
confidence: 99%
“…In the case of PF7, the size of glycosylation is reduced in the double and triple mutations, suggesting that more than one GAG chain could be attached to the peptide. This is consistent with the fact that the size difference between glycosylated agrin and its core protein suggests 3-4 HS side chains (14,18).…”
Section: Constructmentioning
confidence: 99%
“…We hypothesize that the GAG chains of agrin shield agrin and its associated proteins from proteolytic degradation and may be responsible for the slow turnover of amyloid peptide aggregates (11). Tissue culture studies have shown that agrin, when used as a substrate, inhibits neurite outgrowth (13,16,18). It is conceivable that the inhibitory activity of agrin contributes to the localization and termination of axons at particular sites of the muscle basement membrane by slowing the rate of axon outgrowth down.…”
Section: Constructmentioning
confidence: 99%